Development of a Custom Technical Incident and Spare Part Management System for Effective Telecom Network Service Delivery - Falana Jimoh Babalola; Oyelakin Akinyemi Moruff (Journal of Information Technology and Its Utilization, 2024)
Managing technical incident in telecommunication industry is very important in order to ensure business continuity. However, there is a need to find effective ways of managing spare parts when there is a need for the replacement of such spare parts in order to fix technical incidents. That is why telecom operators require relevant systems for adequate incident and spare part management. With the outsourcing arrangement between some  operators and third-party site handlers in Nigeria and most developing countries, there is a need for proper technical incident handling and spare part management. Many of the problems that arise in telecommunication operation come from non-correlation of escalation with the spare part required to restore normal operation of the service after an interruption. This research focuses on designing and developing a web-based system for handling proper management of technical issues and provision of required spare parts promptly as required. This is to ease operations and communications among telecom operators and their technical service providers. The system was built using combination of web development tools such as Jinja Templating Engine, CSS, HTML, JavaScript, JQuery, Python, Flask and SQLite. The developed system has been tested and found useful for the scenarios that it was developed for. The solution allows online management of spares parts, tracking of escalations, provision of fault details and capturing of all faulty equipments due for repairs. It is believed that the custom system can help in achieving effective telecom network service delivery by the company that uses such approach.